Assessment of Soil Carbon Stock and Important Physicochemical Properties in relation to Land use Patterns in Semi-arid Region of Rajasthan, India - Garima Sharma (Journal of the Indian Society of Soil Science, 2022)
A study was conducted to assess the influence of land use type on soil organic carbon (SOC) and related soil properties in the Pushkar valley region of Rajasthan. The ANOVA revealed that within 0-10 cm soil depth, the mean amount of organic carbon (%) and the mean amount of organic carbon stock (t ha-1) were significantly influenced by land use types (F=184.54, p<0.001; F=8.75, p<.001, respectively). At 10-20 cm soil depth, organic carbon content (%) significantly differed among land use classes (F=35.21, p<.001) and also soil carbon stock showed significant variation (F= 8.84, p<.001). At 20-30 cm depth, organic carbon content (%) was affected by land use significantly (F= 44.34, p<.001) whereas, there was no significant difference in carbon stock under land use classes. At 0-30 cm depth, the amount of carbon stock in soil was found in the order: dry deciduous forest (37.78 t ha-1) > tropical thorn forest (28.41 t ha-1) > plantation (31.99 t ha-1) > scrubland (24.91 t ha-1) > cropland (23.22 t ha-1) > fallow land (20.17 t ha-1). The minimum bulk density (1.32 Mg m-3) was recorded at the surface of forest soil, whereas the maximum bulk density (1.47 Mg m-3) was found in the lowest layer of the cultivated land. The present study also revealed a strong negative correlation (p<=0.01) between SOC and bulk density. Principal component analysis (PCA) depicts high variations in soil properties among land uses. Biplot clearly showed that most of the nutrients are higher under soils of the natural forest. Pearson correlation coefficients indicated positive and significant (p<=0.05) correlation between total organic carbon (TOC) and total nitrogen, potassium (K), calcium (Ca), magnesium (Mg) and cation exchange capacity.